(untitled) (Bangladesh Journal of Medical Science, 2011)
Objective: Present study was undertaken to explore the epidemiological and dietary risk factors for hepatitis C disease in Tando Allahyar during June to December 2007. Materials and methods: 140 Hepatitis C patients and 149 controls (age, sex and locality matched with no personal or family history of hepatitis C) were randomly selected from the Tando Allahyar population during June 2007 to December 2007. A standard questionnaire specially developed for that purpose, was distributed among patients and controls. Accurate rapid card test was performed to confirm Hepatitis C virus (HCV) positive or negative patients and controls. O.R with 95% confidence interval was computed and p values were calculated by chi square test. Results: Over all findings showed that among 140 HCV patients 64% were females and 36% males (mean age range was 20-48 years). Our results showed strong positive association of sedentary life style (OR=4, 95% CI, 1.48-10.6, p=0.005), marital status, +ve family history, B+ve blood group, piercing, syringe use (70%), multiple pregnancies (OR=4.72, 95% CI, 1.47-15.15, p=0.008), blood transfusion (OR=4.4, 95% CI, 1.2-14.95, p=0.017), take out food debris by office pins (NS), shave at barber’s shop (NS), dental procedures (NS), medicines used in past (OR=3.08, 95% CI, 1.2-7.71, P=0.016), G.I.T diseases (OR =8.66, 95% CI, 1.28-55.58, p=0.023), stones of kidney or gallbladder, jaundice, Tuberculosis and psychological problems (OR =2.5, 95% CI, 1.04-6.13, P=0.04) with hepatitis C disease. We did not find any association of surgery, BMI, ENT, diseases, meat consumption and smoking with the disease. Vegetables OR =0.842, 95% CI, 0.361-1.964, P=0.694), pulses, tomatoes (OR =0.31, 95% CI, 0.041-2.53, P=0.31), and tea (OR =0.598, 95% CI, 0.251-1.431, P=0.25) were found to be the protective factors for Hepatitis C disease. Conclusion: Sedentary life style, multiple pregnancies, blood transfusion, medicines used in past, G.I.T diseases, and psychological problems are significantly positively associated with Hepatitis C disease. Key words: Hepatitis C disease, HCV infection, epidemiological risk factors, Diet, blood transfusion, G.I.T diseases, and psychological problems. DOI: http://dx.doi.org/ 10.3329/bjms.v10i3.8359 BJMS 2011; 10(3): 163-169